The Effect Of Social Media Instagram @Fikomm.Umby On Fulfilling The Information Needs Of Students - Sholichah, Mar'atus; Hasta, Puti Yasmine Aisyah; Berliansyah, David; Marhaeni, Nafida Hetty; Nastain, Muhamad (Journal of Multidisciplinary Science, 2022)
Instagram is a social media that is used as a source to obtain information, especially for students. The purpose of this study was to determine the influence of social media Instagram @fikomm.umby on the information needs of FIKOMM students. This study uses a quantitative research method with an explanatory approach. The population in this study were 293 students of the Communication Science Study Program, Universitas Mercu Buana Yogyakarta class of 2022, while the sample was taken using a probability sampling technique, namely Simple Random Sampling so that a sample of 170 students was obtained. The data collection technique used a questionnaire on the influence of media use and a questionnaire on fulfilling information needs. The data obtained were analyzed using SPSS Version 20 software. The results showed that there was a strong positive relationship between the use of social media and the fulfillment of student’s information needs. Furthermore, there is a 46.9% influence between the use of social media on meeting student’s information needs. So that the other 53.1% is influenced by other variables that is not examined. The results of the independent sample t-test showed that there was no difference in the effect of using Instagram social media between male and female students.